Suffering, Self-Hate, and the Implicit Association Test: A Critical Assessment into the Zen Philosophy of Cheri Huber - Gold, Jeffrey B. (The international journal of religion and spirituality in society, 2015)
Cheri Huber is a contemporary American Zen Buddhist interested in the relation between self-hate and suffering. Her style is aphoristic, loosely organized, and in her own words, "a swirling mass of notions." My paper organizes her scattered ideas on suffering and self-hate into a coherent system. Her views on self-hate and suffering sometimes makes us uncomfortable. In one of her early works, she points out that, after presenting her thoughts to people, "they tend to not want to talk to us anymore." After explaining her views on self-hate and suffering, I will explain why we occasionally react with uneasiness to her observations. That explanation is based on recent research on hidden and implicit bias.